Efektivitas Model Pembelajaran Station Rotation Dalam Meningkatkan Hasil Belajar Siswa - Egga Priska Lidya; Leny Marlina; Irpinsyah; Sukree Langputeh (PAI RAFAH, 2025)
At SMP Negeri 2 Palembang, the persistent underachievement of students, as indicated by their summative assessments, remains a critical challenge. This issue is not solely attributed to pedagogical strategies but is compounded by classroom dynamics, material misalignment, and ineffective teaching methodologies. In response, the Station Rotation model was introduced to enhance student engagement by rotating them through diverse learning stations, including independent, collaborative, and technology-driven activities. This study aimed to evaluate the effectiveness of the Station Rotation model in improving academic performance. Utilizing a quantitative approach with a True Experimental Design (Posttest-Only Control Design), the research involved 30 students in both the experimental and control groups. Data were collected through tests, observations, and documentation. Results demonstrated a significant improvement in student learning outcomes following the intervention. Prior to the intervention, 63.33% of students were in the medium-performance category, with 20% in the high-performance category. Post-intervention, the medium-performance group increased to 73.33%, while the high-performance group grew to 3.33%. A Paired Samples T-Test yielded a statistically significant result (Sig. (2-tailed) = 0.000), validating the model’s impact. The experimental group’s average test score improved to 83.50, compared to 64.17 in the control group. Additionally, N-Gain analysis supported these findings, revealing a 63.97% improvement in the experimental group (moderate category), compared to a 21.14% increase in the control group (low category). These results underscore the efficacy of the Station Rotation model in enhancing student learning outcomes.